1999
DOI: 10.1046/j.1365-294x.1999.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeography ofDryas integrifolia: glacial refugia and postglacial recolonization

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text direetly trom the original or copy submitted. Thus t sorne thesis and dissertation CXlpies are in typewriter face, while others may be trom any type of computer printer.The quallty of thi. reproduction is dependent upon the quallty of the copy submitted. Broken or indistind print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
3
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 55 publications
4
147
3
1
Order By: Relevance
“…The chloroplast diversity parallels to some extent morphological diversity in the species: three of the four subspecies of S. hirculus have been recorded from Alaska. Recently, molecular evidence has been presented that Dryas integrifolia (Tremblay and Schoen, 1999), and S. oppositifolia (Abbott et al, 2000) survived the Quaternary glaciations in this region, and a hotspot of cpDNA diversity has also been recorded here for Saxifraga cernua . Fossil evidence shows that Beringia was covered by various tundra types in this period (Ritchie and Cwynar, 1982;Edwards et al, 2000), and macrofossils of S. oppositifolia have been found on the northern part of the Seward Peninsula of Alaska during the last full glacial (Goetcheus and Birks, 2001).…”
Section: Amounts Of Haplotype Diversitymentioning
confidence: 60%
See 1 more Smart Citation
“…The chloroplast diversity parallels to some extent morphological diversity in the species: three of the four subspecies of S. hirculus have been recorded from Alaska. Recently, molecular evidence has been presented that Dryas integrifolia (Tremblay and Schoen, 1999), and S. oppositifolia (Abbott et al, 2000) survived the Quaternary glaciations in this region, and a hotspot of cpDNA diversity has also been recorded here for Saxifraga cernua . Fossil evidence shows that Beringia was covered by various tundra types in this period (Ritchie and Cwynar, 1982;Edwards et al, 2000), and macrofossils of S. oppositifolia have been found on the northern part of the Seward Peninsula of Alaska during the last full glacial (Goetcheus and Birks, 2001).…”
Section: Amounts Of Haplotype Diversitymentioning
confidence: 60%
“…Several recent studies have examined the patterns of genetic variation in plant species with arctic distributions (Tremblay and Schoen, 1999;Abbott et al, 2000;Abbott and Brochmann, 2003;Abbott and Comes, 2003). The aim has been to produce evidence bearing on the hypothesised existence of northern refugia, areas in which species may have survived the last glaciation in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported geographic pattern in cpDNA variation below the species level (MAYER et al, 1994;SEWELL et al, 1996;DUMOLIN-LAPÉGUE et al, 1997; VAN DIJK and BAKX-SCHATMAN, 1997;WOLF et al, 1997;KING and FERRIS, 1998;TREMBLAY and SCHOEN, 1990;ABBOTT et al, 2000). Furthermore, intra-specific cpDNA variation has been observed among Fagus species including Fagus sylvatica (DEMESURE et al, 1996), F. crenata (FUJII et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Such studies may reveal the migratory potential of the species in response to climate change. During the Pleistocene glaciations, Arctic plants were restricted to refugia, either within or south of present day Arctic regions, from where they could recolonize areas as conditions improved during interglacial periods (172,173). The rate of colonization by different species during the Holocene probably depended on where their closest refugia were situated, their dispersal biology and genetic makeup.…”
Section: Plantsmentioning
confidence: 99%